The Effect of Highland and Lowland Living on Cardiovascular Ability: a Literature Review - Poni Purnama; Arsil Arsil; Syahrastani Syahrastani; Bafirman bafirman; Fiky Zarya (Postgraduate, University of Mataram, 2023)
This study aims to review the literature related to the influence of living in highlands and lowlands on cardiovascular ability. Highlands, with an altitude of more than 2,500 meters above sea level, have unique environmental characteristics such as lower oxygen levels, lower air pressure, and cooler temperatures. In contrast, lowlands typically have more stable conditions and higher oxygen levels. These environmental differences are believed to have a significant impact on an individual's cardiovascular ability. In this literature review, we evaluated various studies comparing cardiovascular parameters such as aerobic capacity, VO2 max, resting heart rate, and other physiological adaptations between populations living in highlands and lowlands. The results of various studies show that individuals living at high altitudes tend to have better physiological adaptations in terms of oxygen use efficiency and higher aerobic capacity. This is due to the body's adaptation to chronic hypoxia, which increases red blood cell production and oxygen transport efficiency. However, there are also some higher cardiovascular challenges at high altitudes, such as an increased risk of pulmonary hypertension and heart disease. In contrast, low-lying populations generally show more stable cardiovascular parameters but are less adaptive to hypoxia conditions. In conclusion, living at high altitudes and lowlands exert different influences on cardiovascular ability, with each environment providing its own advantages and challenges. More research is needed to understand deeper adaptation mechanisms and their implications for long-term cardiovascular health